The adventures of Tintin : The calculus affair - Hergé (Little, Brown, 2008)
In volume 6, the book continues to take readers into the exciting and dramatic adventures of Tintin and his close group of friends. Across continents and in every situation, Tintin, Snowy the dog along with Captain Haddock and Professor Calculus are ready to face challenges and dangers. From investigating mysterious plots to exploring the wilderness, this book offers readers a rich, diverse and vibrant series of stories.